Characteristics of measles in children during the rise in incidence in 2019 - O. V. Molochkova; O. B. Kovalev; M. A. Kosyreva; N. O. Ilyina; O. V. Shamsheva; E. N. Getmanova; A. A. Korsunsky; E. V. Galeeva; A. A. Guzhavina (Детские инфекции (Москва), 2022)
In Moscow, as in Russia, in 2019 there was an increase in the incidence of measles in recent years.Purpose: to analyze the course of measles in children hospitalized in 2019 during the period of rising incidence.Materials and methods: a retrospective analysis and statistical processing of 30 case histories of children hospitalized with measles in the infectious diseases department of the Children's City Clinical Hospital № 9 named after G.N. Speransky in 2019.Results: More than half of the patients were under the age of 3 years (53%). In 90% of cases, the sick were not vaccinated, in 73% – due to the refusal of their parents. Only 23% of patients had measles contact, mostly familial. Measles in hospitalized children proceeds typically, in 83.3% of cases in a moderate form, with characteristic pathognomonic symptoms: in 83.3% of patients, Belsky-Filatov-Koplik spots are detected, on average, on the 4.4 ± 0.8 day of illness, spotted – papular rash on the face with staged distribution and subsequent staged pigmentation in all patients. Complications develop in 66.7% of cases, more often pneumonia (36.7%) and obstructive bronchitis (20%), which in 16.7% of cases cause the severity of the course and lead to the development of emergency syndromes and conditions (respiratory failure, obstructive syndrome).Conclusions. Failure to vaccinate against measles contributes to morbidity with possible complications.